Autophagy and Exosomes in the Aged Retinal Pigment Epithelium: Possible Relevance to Drusen Formation and Age-Related Macular Degeneration - Wang, Ai Ling (Public Library of Science, 2009)
Age-related macular degeneration (AMD) is a major cause of loss of central vision in the elderly. The formation of drusen, an extracellular, amorphous deposit of material on Bruch's membrane in the macula of the retina, occurs early in the course of the disease. Although some of the molecular components of drusen are known, there is no understanding of the cell biology that leads to the formation of drusen. We have previously demonstrated increased mitochondrial DNA (mtDNA) damage and decreased DNA repair enzyme capabilities in the rodent RPE/choroid with age. In this study, we found that drusen in AMD donor eyes contain markers for autophagy and exosomes. Furthermore, these markers are also found in the region of Bruch's membrane in old mice. By in vitro modeling increased mtDNA damage induced by rotenone, an inhibitor of mitochondrial complex I, in the RPE, we found that the phagocytic activity was not altered but that there were: 1) increased autophagic markers, 2) decreased lysosomal activity, 3) increased exocytotic activity and 4) release of chemoattractants. Exosomes released by the stressed RPE are coated with complement and can bind complement factor H, mutations of which are associated with AMD. We speculate that increased autophagy and the release of intracellular proteins via exosomes by the aged RPE may contribute to the formation of drusen. Molecular and cellular changes in the old RPE may underlie susceptibility to genetic mutations that are found in AMD patients and may be associated with the pathogenesis of AMD in the elderly.